The presence of missed care: A staff development response. (20th July 2022) - Blackman, Ian; Shifaza, Fathimath; McNeill, Liz; Willis, Eileen; Verrall, Claire; Henderson, Julie
Abstract: Aims: This study quantifies the types and frequencies of missed care identified by nurses and measures its impact on their capacity to demonstrate mandatory practice standards as future hospital staff. Background: Considerable literature exists as to the nature of missed care but there is a paucity of findings about how missed care impacts on learning firstly as a student and then as a graduate nurse employed in a hospital setting. Additionally, there is little emphasis as to how staff development for nurses exposed to missed care may be implemented. Methods: A non‐experimental research design using self‐audit data was selected to collect information about the types and frequencies of missed care from nurses engaging in clinical experience. A convenience sample of 471 nursing students completing their undergraduate nursing degree programme was explored. A multi‐variate statistical approach was used to apply and then model the consensus scores of undergraduate nurses' beliefs about the frequency of missed care. Implications for their developing competence in critical thinking, therapeutic communication and maintaining capacity for professional practice has been considered. Results: Eight variables directly affect student's total scores underpinning their understanding of missed care and their ability to meet professional standards of practice, given their exposure to care omission. These factors reflect differing nurse attributes, the nature of the clinical venues and shift times, preceptor type, student satisfaction with work teams and staffing adequacy. Conclusions: Modelling outcomes suggest possible changes to hospital staff development learning programme content, learning processes and how it may be better delivered through to minimize episodes of missed care. Implications for Nursing Management: Staff development needs to note that nursing staff believe missed care occurs across all three‐patient acuity domains with patient observation, education, support, and timely medication administration being most frequently omitted. Different clinical venues within the hospital sector and shift times vary in nurses' exposure with missed care. Student nurses' learning and associated development of practice standards is impacted by prior exposure to missed care during clinical placement. Non‐native English‐speaking nurses require greatest learning support in the presence of missed care. As missed care can be predicted, remedial changes to the nurse staff development program content and learning processes can be orchestrated.